Socio-economic assessment of seaweed farmers in Tamil Nadu - A case study in Ramanathapuram District - Narayanakumar, R.; Krishnan, M. (Indian Journal of Fisheries, 2013)
Seaweed mariculture is an economically viable livelihood option for the coastal fi shing community especially for the fi sherwomen. In Tamil Nadu, along the south-east coast of India, the organised seaweed farming on an industrial scale was initiated by the Pepsi Holdings India Private Limited (Pepsi Co) in 2000 in Gulf of Mannar in Ramanathapuram District. After proving the economic viability of seaweed farming, Pepsi Co modifi ed its business model in 2003 by organising the fi shers to take up seaweed farming on contract basis through Self Help Groups (SHGs). In this paper, an assessment of the socio-economic status of seaweed farmers in Ramnathapuram District of Tamil Nadu has been made, which is the pioneering district in India in seaweed farming. Fishing and seaweed farming are the most important occupations in this district. The average family size of respondents for the present study ranged from 4.5 in Mandapam to 5.5 in Rameswaram. Signifi cant structural changes have taken place in the socio-economic status of many fi shermen who have taken up seaweed farming over the last 10 years. In Ramanathapuram, seaweed farming is estimated to provide employment to the tune of 7,65,000 man days per annum based on the District’s plan. The gains, hitherto realised through the SHG model of seaweed farming, should be consolidated with consistent institutional and fi nancial support to the seaweed farmers.